2005
DOI: 10.3748/wjg.v11.i11.1634
|View full text |Cite
|
Sign up to set email alerts
|

A Thai family with hereditary pancreatitis and increased cancer risk due to a mutation inPRSS1gene

Abstract: AIM:To investigate mutation of serine protease 1-cationic trypsinogen (CT, PRSS1) gene in members of a Thai family with hereditary pancreatitis and pancreatic cancer. METHODS: Polymerase chain reaction and directsequencing were performed to analyze the PRSS1 gene in two members of the family affected by pancreatitis. Allele specific amplification (ASA) method was then developed to detect the mutation of the PRSS1 gene in all available members of the family and normal control subjects. RESULTS:A cytosine (C) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…This relatively rare mutation has been previously identified among patients of widely varying ethnicities such as Thais, Turks and Europeans (Le Maréchal et al, 2001; Tautermann et al, 2001; Teich et al, 2002; Pho-Iam et al, 2005) and here we confirm its association with autosomal dominant hereditary pancreatitis in a German kindred. Moreover, we demonstrate that mutation induced misfolding of cationic trypsinogen results in intracellular retention and decreased secretion.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…This relatively rare mutation has been previously identified among patients of widely varying ethnicities such as Thais, Turks and Europeans (Le Maréchal et al, 2001; Tautermann et al, 2001; Teich et al, 2002; Pho-Iam et al, 2005) and here we confirm its association with autosomal dominant hereditary pancreatitis in a German kindred. Moreover, we demonstrate that mutation induced misfolding of cationic trypsinogen results in intracellular retention and decreased secretion.…”
Section: Introductionsupporting
confidence: 89%
“…Teich et al (2002) identified the p.R116C mutation in a pediatric patient with recurrent acute pancreatitis and in her unaffected mother. More recently, Pho-Iam et al (2005) described a Thai family with hereditary pancreatitis in which the p.R116C mutation was present in three affected (mother, son, mother’s sister) and one unaffected (mother’s brother) members.…”
Section: Resultsmentioning
confidence: 99%
“…Internationally, the majority of PRSS1 kindreds have been identified in the USA (13, 29, 30) and Europe (4, 31, 32), though few have also been reported from Japan (33), South America (34, 35), and Thailand (36). To date, HP has not been reported in patients of African ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…There is a proven association between carcinoma of the pancreas and both the sporadic (chiefly tropical calcifying pancreatitis [68]) and hereditary forms of CP (chiefly due to mutations in the PRSS1 [69] and cationic trypsinogen gene [70]), the standardized incidence ratio for development of PC in CP cases being 14–18, which is further increased by cigarette smoking [70]. Results from a prospective case-control study [71] seem to suggest that CP may be closely related to PC, although the answer to the question of a cause-and-effect relationship is not clear (the link between CP and PC was discussed in a recent article [72]).…”
Section: Risk Factors and Their Role In Pancreatic Cancer Screeninmentioning
confidence: 99%